DIRECT AND INDIRECT TAXATION AND ITS ROLE IN REDUCING THE BUDGET DEFICIT. CASE STUDY - Alina MARCUTA; Cristiana TINDECHE; Cosmina SMEDESCU; Dragos SMEDESCU; Liviu MARCUTA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Fiscal policy represents a problem of security and solidarity at the level of each individual state, but also at the community or world level, because ensuring tax revenues can contribute to ensuring economic, social and environmental stability, but at the same time it also contributes to economic development both current, as well as future generations. This can be achieved by improving some important sectors of activity, such as education or health. Each individual state establishes a certain fiscal policy, adapted to its own needs, in which the ratio between direct taxation and indirect taxation, the manner of their application can ensure sufficient fiscal revenues to cover both public expenses, but also allow the achievement of investments. The purpose of this paper is to analyze the two taxation systems, both at the level of Romania and at the level of other EU countries, with the aim of making comparisons and finding solutions regarding the way to improve the fiscal policy in Romania. The research methodology assumed both the analysis of the specialized literature regarding the characteristics of fiscal policies and their role in ensuring economic development, as well as the consultation of internal and international databases from which fiscal information was collected regarding direct taxes and indirect taxes. The data collected and systematized were subjected to an analysis with the help of some statistical indicators. The interpretation of the results allowed us to formulate conclusions that highlighted the fact that although Romania registers a GDP/inhabitant that places it very close to the average of EU countries (72%), in terms of the contribution of tax revenues in the formation of GDP, there is an imbalance, as a result of the weight of 26.3%. This imbalance is due to several factors, among which we were able to identify: low level of collection of fees and taxes to the state budget, granting exemptions from paying taxes or applying preferential fiscal regimes, permanent changes to the Fiscal Code, etc., aspect that, in addition to excessive financing of consumption, contributed to the appearance of the budget deficit.